PERANCANGAN SISTEM PEMBANGKIT LISTRIK TENAGA SURYA MENGGUNAKAN PVSYST DI GEDUNG LABORATORIUM SENTRAL ILMU HAYATI UNIVERSITAS BORNEO TARAKAN - Huda, Abil; Haslinda, Haslinda (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Borneo Tarakan, 2025)
The increasing need for energy encourages the use of renewable energy, one of which is solar energy. This study discusses the design of a rooftop PLTS system at the Central Laboratory of Life Sciences (LSIH) Building, Borneo Tarakan University. Using PVsyst software, the technical design of the system is simulated to adjust to the actual load needs of the building. The design results show the use of 32 250Wp solar modules and 2 inverters with a total output power of 8.2 kWh. This system is capable of supplying 8 kWh of power and producing energy up to 11,958 kWh/year.